How are the meso-level expert organizations connected to farmers and among themselves? Comparing Rakai (Uganda) and Lushoto (Tanzania) - Jha, Yamini; Welch, Eric W.; Ogwal-Omara, Richard; Halewood, Michael (2016)
Key messages: Network analysis provides a mechanism to both understand how information and communication structures vary across sites, and to identify opportunities for intervening in ways that may improve communication flows. Farmer-expert network structures differ between Lushoto and Rakai. Farmers and expert organizations are more directly connected in Lushoto than in Rakai. This may mean that Lushoto farmers have more immediate access to climate smart technologies and information. District level expert organizations are more interconnected in Rakai compared to Lushoto. However, local level expert organizations are more connected in Lushoto. These findings may indicate opportunities for improved connections at the local and district levels in Rakai and Lushoto, respectively. This comparative analysis shows that Rakai communication networks could be improved through better connections among local experts and between experts and farmers.